Contribution of cohort studies in the analysis of oral health in children and adolescents in Sobral, Ceará - Luiz Roberto Augusto Noro; Angelo Giuseppe Roncalli; Ana Karine Macedo Teixeira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
The main objective of this study was to identify the oral health status of the child population in a northeastern Brazilian municipality as a strategy to carry out subsequent longitudinal studies to investigate the main determinants of oral diseases in the specific age groups of teenagers and young adults. Epidemiological investigations and interviews were conducted in households by research teams. In the first study, a DMFT (decayed, missing, and filled teeth) score of 1.66 was found for 9-year-olds; although only 23% children aged between 5 and 6 years were caries-free, 32.7% had gingival bleeding and 9.5% were diagnosed with severe malocclusion problems. The second wave of the cohort indicated that the incidence of caries increased progressively according to age, from 1.60 in 12-year-old adolescents to 2.28 in those aged 15. Toothache in the past 6 months, maternal income and school meals, adjusted for the perception of need for treatment, maternal education, and dental visit at least once were the variables associated with high incidence of dental caries. Data collection for the third wave of the cohort is currently underway. Socioeconomic factors and access to health services were associated with the incidence of caries.